RentWise: An Updated Tool for Meeting the Needs of Renters - Lori A. Hendrickson; Rebecca A. Hagen Jokela; Shawna F. Thompson ([TEST] Journal of Extension, 2021)
Housing education is critical in the context of today’s economy. This article details the current need for rental education for both consumers and practitioners. We discuss the importance of housing education resources for Extension educators across the United States, describe the updated curriculum RentWise, and provide information related to accessing the curriculum.
Keywords: RentWise; rental housing; housing; tenant education; renters